Edukasi Faktor Risiko Dan Deteksi Dini Penyakit Jantung Koroner Untuk Masyarakat Rentan Di Posyandu Lansia Kelurahan Mangliawan Kabupaten Malang - Leny Candra Kurniawan; Ikhwan Abdullah; Widia Shofa Ilmiah (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The causes of death number one in the world is Coronary Heart Disease (CHD), including in Indonesia. WHO data indicates that 17 million people die each year from cardiovascular diseases, with CHD being the largest contributor. The prevalence of heart disease in Indonesia reaches 0.85% of the total population and causes approximately 651,481 deaths annually in Indonesia. Many elderly individuals lack adequate knowledge about CHD and its risk factors. The Mangliawan village in Malang Regency has a relatively high population of elderly residents. The aim of this activity is to provide education on risk factors and early detection of CHD to vulnerable communities at the elderly health posts. The implementation method included preparation stages with a pre-test, conduction stages involving education delivery, and evaluation stages with a post-test. Instruments include a questionnaire, leaflets, posters, blood pressure monitors, blood glucose and cholesterol checks, and weight scales. The results of this activity showed that there was an increase in knowledge with an average score above 85% of participants. The conclusion of the activity indicates that there are success in the implementation of this education, evidenced by the increase in knowledge levels between the pre-test and post-test.